Growth and Yield Response of Shallot (Allium ascalonicum L.) to Various Concentrations of Eco-Enzyme Fertilizer: English - Swati Sembiring; Lita Nasution; Dedi Holden Simbolon; Magdalena Saragih; Donatus Dahang; Rajiv Ginting; Juliana Simbolon; Yolanda Febrima Tarigan; Rifa Diah Valahsya Sembiring; Indra Prabowo Pandiangan; Eristo Syahmana Tarigan; Sri Rejeki Silaban (Argael Publisher, an imprint of CV. ARGA FARMA, 2026)
Shallot (Allium ascalonicum L.) is a horticultural commodity with high economic value, but its productivity is often constrained by declining soil fertility associated with prolonged and intensive inorganic fertilization. This study evaluated the growth and yield response of shallot to various eco-enzyme fertilizer dosages and identified the most effective dosage under polybag-based open-field experimental conditions. The experiment was arranged in a non-factorial Randomized Complete Block Design (RCBD) with five treatments and five replications: E0 (without eco-enzyme), E1 (100 mL plot⁻¹), E2 (200 mL plot⁻¹), E3 (300 mL plot⁻¹), and E4 (400 mL plot⁻¹). Each plot referred to one polybag experimental unit. The observed variables were plant height, number of leaves, number of tillers, fresh bulb weight, and dry bulb weight. The results showed that eco-enzyme dosage affected several vegetative variables at specific observation times, but the response was not uniform across all growth stages. E2 produced the highest plant height at 14, 28, and 42 days after planting (DAP), whereas E3 produced the highest leaf number at 28 DAP. Yield formation was more favorable under the lowest eco-enzyme dosage. Treatment E1 produced the highest fresh bulb weight (167.2 g plot⁻¹) and dry bulb weight (131.2 g plot⁻¹), corresponding to approximately 5.03% and 19.06% increases over the control, respectively. These findings indicate that 100 mL plot⁻¹ was the most efficient eco-enzyme dosage for improving bulb yield of Bima Brebes shallot under the conditions of this experiment.